A Study On The Effect Of Machining Parameters On The Surface Roughness Of Aluminum Alloy Castings Obtained By Evaporative Pattern Casting (Epc) Process - Omidiji, V. (Ife Journal of Technology, 2019)
In this study, the effect of machining parameters on the integrity of aluminum alloy obtained by evaporative casting pattern (EPC) process was considered. The pattern, gating system and mould were designed for the casting process. Three process parameters used in generating the Taguchi’s code for the analysis of the surface roughness are the pouring temperature, grain finest number of the moulding material and the gating ratio. The analysis revealed that the best surface finish of aluminium alloy was obtained at 650°C. At temperature higher than this, casting obtained have very rough surfaces with more defects. The Taguchi codes generated lead to nine numbers of runs, and the results of surface roughness gotten under the examination of computer numeric control (CNC) machine were analysed by statistical analysis software (Minitab). The effect of speed decreases with the increase in speed, the effect of feed rate gives a better finish at 90mm/min while the parameter depth of cut gives a reasonable result between 0.5 to 1.0 mm. In the analysis, it was discovered that machining parameters also have significant effect on the surface roughness of cast aluminium alloy.